2019
DOI: 10.17816/uroved935-11
|View full text |Cite
|
Sign up to set email alerts
|

The level of nerve growth factor and its relationship with the content of leukocytes and mast cells in experimental interstitial cystitis/painful bladder syndrome

Abstract: Relevance. Interstitial cystitis/painful bladder syndrome (IC/PBS) is a debilitating condition of pain and discomfort in the bladder. Due to the limited number of published studies in this area, there is a need for further research. Objective: to evaluate the level of nerve growth factor and its relationship with various types of leukocytes and mast cells of the bladder tissue in animals with experimental models of interstitial cystitis/painful bladder syndrome. Material and methods. IC/PBS modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Interestingly, a recent study showed that activation of MCs by NLRP3 contributed to the development of endometriosis (54). Further, high levels of infiltration by MCs occur in response to the damage to bladder integrity due to frequent urinary toxicity in IC (55). In our study, we observed a significant increase in the number and frequency of MCs in the UB after CYP induction that was suppressed by Dap treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, a recent study showed that activation of MCs by NLRP3 contributed to the development of endometriosis (54). Further, high levels of infiltration by MCs occur in response to the damage to bladder integrity due to frequent urinary toxicity in IC (55). In our study, we observed a significant increase in the number and frequency of MCs in the UB after CYP induction that was suppressed by Dap treatment.…”
Section: Discussionsupporting
confidence: 56%